Excess of topological defects induced by confinement in vortex nanocrystals - Cejas Bolecek, N.R.; Dolz, M.I.; Pastoriza, H.; Konczykowski, M.; van der Beek, C.J.; Kolton, A.B.; Fasano, Y.; Fasano, Yanina (American Physical Society, 2017)
Fil: Cejas Bolecek, N.R. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina